2019
DOI: 10.1016/j.arabjc.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Sterols from the brown alga Cystoseira foeniculacea: Degradation of fucosterol into saringosterol epimers

Abstract: The present study was carried out in order to determine the phytochemical composition of the marine brown alga Cystoseira foeniculacea collected off the coasts of Algeria. After a preliminary fractionation of its organic crude extracts by column chromatography, the resulting fractions were further analysed by 1 H NMR. Even though algal species of the genus Cystoseira are commonly known to produce a wide variety of meroditerpenoids, in the case of C. foeniculacea none of the fractions were found to contain such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The lipid yields for each extraction method for the two species are presented in 4reported that lipids were not present in large proportion in algae compared to other constituents. Regarding the genus Cystoseira, these levels are considered to be lower than those obtained from C. foeniculacea (22) and C. osmundacea (23). In L. papillosa, a species of the genus Laurencia, a comparable result in total lipids was obtained (24).…”
Section: Lipids Extraction Yieldmentioning
confidence: 99%
“…The lipid yields for each extraction method for the two species are presented in 4reported that lipids were not present in large proportion in algae compared to other constituents. Regarding the genus Cystoseira, these levels are considered to be lower than those obtained from C. foeniculacea (22) and C. osmundacea (23). In L. papillosa, a species of the genus Laurencia, a comparable result in total lipids was obtained (24).…”
Section: Lipids Extraction Yieldmentioning
confidence: 99%
“…Brown algae are chemically insufficiently characterized. Some studies reported the determination of sterols in brown algae (4). Cystoseira sp, are mostly used for the extraction and purification of alginates (5).…”
Section: Introductionmentioning
confidence: 99%
“…The extracts were then partitioned via solvent fractionation [13,25]. After solvent dissolution under reduced pressure, the organic extracts were fractionated using silica gel column chromatography with a mixture of solvents of increasing polarity [14,22,23,26]. The fraction was eluted using a solvent to remove fatty acids, which were then analyzed further [26].…”
Section: Characteristics and Structure Of Fucosterolmentioning
confidence: 99%